Perceptions and Meaning-Making of ‘Shariah Security’ Among Muslim Digital Natives in the Use of Blockchain-Based Financial Platforms - Muhammad Iqbal; Izra Berakon (WISE Pendidikan Indonesia, 2025)
This study explores how Muslim digital natives perceive and construct the meaning of Shariah security in their engagement with blockchain-based financial platforms. Using an Interpretative Phenomenological Analysis (IPA), data were gathered through in-depth interviews and digital artifacts from 20 participants actively using decentralized financial applications. Findings reveal that Shariah security is understood as a multidimensional construct integrating spiritual–moral assurance, ethical–procedural integrity, and technical–operational protection. Trust in blockchain emerged as a negotiated outcome shaped by religious identity, technological literacy, and community-mediated discourse. Participants’ engagement with blockchain was closely tied to processes of techno-religious identity construction, while social media functioned as a primary epistemic environment shaping perceptions of Shariah compliance. Emotional responses, such as reassurance, anxiety, and empowerment, further influenced security judgments. The study contributes a user-centered framework for understanding Shariah-oriented meaning-making in digital finance and offers implications for designing culturally aligned fintech ecosystems.